PELAKSANAAN TUPOKSI KEPALA DESA DALAM MENCIPTAKAN KETENTRAMAN DAN KETERTIBAN DI DESA KOTO CENGAR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Yuwandi Setiawan; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The village head as the head of government in the scope of the village should be able to perform optimum duties, either as a public servant or as an intermediary who can provide solutions to problems that exist within the community that includes the area of authority. The aspirations conveyed by the community must be heard by a village head so that what is the goal can be achieved in accordance with expectations. But in the reality of the field is still a lot of problems, this is due to lack of implementation of the head of the Lead Countryside tupoksi.The purpose of this research is to know the implementation of tupoksi village head in koto cengar village in creating peace and order as well as what factors hamper the implementation of tupoksi village head in creating peace and order in koto cengar village. To analyze the phenomenon in this study the authors use Winardi theory with appropriate time utilization indicators, the amount of output, willingness to cooperate, quality of work. The method used in this research is descriptive with qualitative approach.Results of this study show the implementation of the tupoksi village head in creating peace and order in the village koto cengar kuantan mudik district Kuantan singingi district has not been done well with the existence of several cases that disturb the peace and order of society. The inhibiting factors found were communication, human resource placement, facilities and infrastructure, factors of society.Keyword : Implementation of Tupoksi, Lead countryside, peace and order